2018
DOI: 10.29164/18animals
|View full text |Cite
|
Sign up to set email alerts
|

Animals

Abstract: This text is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License. For image use please see separate credit(s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Working from a different tradition, the anthropology of animals has been focused less on such normative models, and more on everyday human‐animal relations. Where early anthropological research on animals understood them mostly as symbols (Mullin, 1999; White and Candea, 2018), recent multispecies ethnography has sought to understand animals more agentively, drawing attention to their cognitive, emotional, and communicative capacities and emphasizing their active role in developing relationships with humans and places (e.g., Kirksey and Helmreich, 2010; Ogden, Hall, and Tanita, 2013; Porter and Gershon, 2018). This scholarship draws on new materialism and actor‐network theory and does not see agency as the unique property of human actors, or even as restricted to self‐directed, future‐oriented intentional action.…”
Section: From Citizenship To More‐than‐human Denizenshipmentioning
confidence: 99%
“…Working from a different tradition, the anthropology of animals has been focused less on such normative models, and more on everyday human‐animal relations. Where early anthropological research on animals understood them mostly as symbols (Mullin, 1999; White and Candea, 2018), recent multispecies ethnography has sought to understand animals more agentively, drawing attention to their cognitive, emotional, and communicative capacities and emphasizing their active role in developing relationships with humans and places (e.g., Kirksey and Helmreich, 2010; Ogden, Hall, and Tanita, 2013; Porter and Gershon, 2018). This scholarship draws on new materialism and actor‐network theory and does not see agency as the unique property of human actors, or even as restricted to self‐directed, future‐oriented intentional action.…”
Section: From Citizenship To More‐than‐human Denizenshipmentioning
confidence: 99%
“…By recognising nonhuman agency, it tries to take anthropology beyond the constraints of anthropocentrism (Locke, 2018), and argues that species are always multiple, multiplying their forms and associations. These conceptual directions had earlier resulted in the development of a new genre of writing and mode of research-multispecies ethnography-taking beings and other-than-human selves as ethnographic subjects, intertwined and shaped by political, economic and cultural forces (Kirksey and Helmreich, 2010;van Dooren et al, 2016;White and Candea, 2018). Multispecies ethnography proposes to develop epistemologically modified and ecologically sensitive research and writing that is 'attuned to life's emergence within a shifting assemblage of agentive beings' (Ogden et al, 2013, p. 6).…”
Section: Question Of the 'Other'mentioning
confidence: 99%
“…Ontological approaches in anthropology have revealed that the realm of sociality in many Indigenous societies in the world is not confined to the human domain but is extended beyond humanity to encompass animals, plants, spirits, and other entities. In the past several decades, great efforts have been made on studies of relational interactions between humans and animals in the Arctic, Amazonia, and North Asian regions (see White and Candea 2018). However, the relation between living humans and deceased ancestors has largely been neglected.…”
Section: Introductionmentioning
confidence: 99%